Improving Cow-Calf Profitablity through Enterprise Analysis - Jones, Rodney D.; Simms, Danny D. (My University, 1997)
This publication highlights the importance of cow-calf enterprise analysis and provide an overview of the records needed and implementation of a complete cow-calf enterprise analysis.
MF2259_1997_04
Keywords: MF2259; Livestock; Economics; MF